Acute effects of different training loads on affective responses in resistance-trained men - Ribeiro, A. S.; dos Santos. E. D.; Nunes, J. P.; Schoenfeld, B. J. (International Journal of Sports Medicine, 2019)
The main purpose of the present study was to investigate the acute effects of different training loads on ratings of perceived exertion and discomfort and feelings of pleasure/displeasure in resistance-trained men. Twelve resistance-trained men (26.7±3.5 years, 85.1±17.5 kg, and 174. 9±9.9 cm) performed 3 sets of the bench press, squat on a hack machine, and lat pulldown, until volitional concentric failure in two separate conditions: a moderate load (MOD) consisting of a relative load of 8-12 repetitions maximum (RM), and a light load (LIT) consisting of a relative load of 25-30RM. The session rating of perceived exertion (sRPE), session rating of perceived discomfort (sRPD), and session pleasure/displeasure feelings (sPDF) were assessed after 15 min after the ending of each session. A randomized, counterbalanced, crossover study was performed with 48 h recovery afforded between sessions. Differences between conditions were observed for sRPE and sRPD, in which scores for LIT were greater than MOD (sRPE: MOD=5.5±1.0 vs. LIT=6.4±0.7; sRPD: MOD=6.7±1.7 vs. LIT=8.7±1.0). For sPDF, MOD reported feelings of pleasure (1.2), whereas the LIT presented a feeling of displeasure (-2.3). Results suggest that resistance training performed with a light load until failure induces higher degrees of effort, discomfort and displeasure compared to a moderate load.